Partners’ Independence in Core Discussion Networks. Native Endogamous, Foreign-born Endogamous and Mixed Couples in Spain - De-Miguel-Luken, Verónica (My University, 2019)
The study of immigrants’ personal networks is gaining increasing attention in recent years, mostly in relation to the social support provided and received in different moments of ego’s migratory experience and various geographical contexts. On the other hand, in last decades literature has widely analysed core discussion networks, where homophily based on ethnic origin has been proved to be of enormous relevance. However, there are still some gaps in the knowledge about the precise position of spouses and intimate partners in these core networks when the ethnic component is taken into account and, to our knowledge, there is hardly any research that has considered together both partners’ perspectives. In this research, we use a nationally representative sample for Spain that contains information about both members of the couple’s core discussion networks. This allows us to focus simultaneously on these networks for both members of the cohabitant couples. Specifically, we compare three types of couples: native endogamous, mixed (Spaniard – non Spaniard) and foreign-born endogamous, in order to answer the following research questions: a) Does the partner’s role differ according to type of couple? (partner being elicited or not, and the extent to which ego can discuss important matters with him/her) b) What degree of independence exists between the partners in terms of non-shared alters? Is it affected by partners’ national origins? c) How is network density related to couple types? How can it influence partners’ independence? In order to answer question a) we use multilevel modelling (alters nested within egos, who are nested within couples) and, for question b), we build a variable about alters overlap that refers to the couple as a unit of analysis, so conventional multivariate regression models are applied. Preliminary results show that the role of the partner varies according to type of couple.
Keywords: Inmigrantes-Situación social; Mixed couples; Relational vulnerability; Multilevel models; Network analysis; Personal networks; Core discussion networks